The trend of RFID application to the supply chain management (2009-2010): a text mining analysis. (6th August 2010) - Wu, S.H.; Shi, Y.D.
In recent years, much research has been devoted to the exploration of the application of RFID to the supply chain management; however, few have deployed the study of the trend of RFID application. In fact, grasping the trend of the RFID application in the supply chain management is imperative for enterprises and researchers. The study aims at exploring the trend change of the RFID application from the year of 2009 to 2010. The contribution of the study includes the following two points. First, the study has found the shift of the RFID application from the technological focus to the topics of system and companies usage. Second, the study finds a new way of literature survey by using the text mining method in order to explore the trend change.